2004
DOI: 10.1111/j.0953-816x.2004.03177.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coadministration of cannabinoids and morphine on nociceptive behaviour, brain monoamines and HPA axis activity in a rat model of persistent pain

Abstract: The antinociceptive effects of Delta9-tetrahydrocannabinol (Delta9-THC) have been widely described; however, its therapeutic potential may be limited by secondary effects. We investigated whether coadministration of low doses of cannabinoids or cannabinoids and morphine produced antinociception in the absence of side-effects. Effects of preadministration (i.p.) of Delta9-THC (1 or 2.5 mg/kg), cannabidiol (5 mg/kg), morphine (2 mg/kg), Delta9-THC + morphine, Delta9-THC + cannabidiol or vehicle on formalin-evoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
70
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 57 publications
(98 reference statements)
6
70
0
Order By: Relevance
“…The antinociceptive effects of THC and CP55940 in the present study agree with a large literature showing that cannabinoid agonists produce antinociception in nearly all assays of pain-stimulated behavior (for recent reviews, see Rice, 2006;Karst et al, 2010). For example, previous studies in rodents have shown that cannabinoid agonists decreased stretching elicited by intraperitoneal acid administration (Sofia et al, 1975;Anikwue et al, 2002;Booker et al, 2009), first and second phases of nociceptive behavior elicited by intraplantar formalin injection (Finn et al, 2004;Khodayar et al, 2006), tail-flick/paw-withdrawal responses elicited by noxious heat (Lichtman and Martin, 1991;De Vry et al, 2004;Wiley et al, 2007), and hypersensitive withdrawal responses elicited by thermal/mechanical stimuli in inflammatory or neuropathic pain models (Cheng and Hitchcock, 2007;Elikkottil et al, 2009;Sain et al, 2009). As in the present study, cannabinoid antinociception is often shown to be dose-and/or time-dependent, and sensitivity to rimonabant antagonism or genetic knockout of cannabinoid 1 receptors has been interpreted as evidence of cannabinoid 1 receptor mediation (Monory et al, 2007;Booker et al, 2009).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…The antinociceptive effects of THC and CP55940 in the present study agree with a large literature showing that cannabinoid agonists produce antinociception in nearly all assays of pain-stimulated behavior (for recent reviews, see Rice, 2006;Karst et al, 2010). For example, previous studies in rodents have shown that cannabinoid agonists decreased stretching elicited by intraperitoneal acid administration (Sofia et al, 1975;Anikwue et al, 2002;Booker et al, 2009), first and second phases of nociceptive behavior elicited by intraplantar formalin injection (Finn et al, 2004;Khodayar et al, 2006), tail-flick/paw-withdrawal responses elicited by noxious heat (Lichtman and Martin, 1991;De Vry et al, 2004;Wiley et al, 2007), and hypersensitive withdrawal responses elicited by thermal/mechanical stimuli in inflammatory or neuropathic pain models (Cheng and Hitchcock, 2007;Elikkottil et al, 2009;Sain et al, 2009). As in the present study, cannabinoid antinociception is often shown to be dose-and/or time-dependent, and sensitivity to rimonabant antagonism or genetic knockout of cannabinoid 1 receptors has been interpreted as evidence of cannabinoid 1 receptor mediation (Monory et al, 2007;Booker et al, 2009).…”
supporting
confidence: 91%
“…As in the present study, cannabinoid antinociception is often shown to be dose-and/or time-dependent, and sensitivity to rimonabant antagonism or genetic knockout of cannabinoid 1 receptors has been interpreted as evidence of cannabinoid 1 receptor mediation (Monory et al, 2007;Booker et al, 2009). It is generally appreciated that nonselective behavioral depression may confound measures of cannabinoid antinociception in assays of pain-stimulated behavior (De Vry et al, 2004;Finn et al, 2004), and in the present study, THC and CP55940 produced evidence of nonselective behavioral depression insofar as they decreased ICSS in the absence of pain. However, THC-induced depression of acid-stimulated stretching was longer lasting than THC-induced depression of control ICSS.…”
supporting
confidence: 50%
See 1 more Smart Citation
“…Thus, for example, additive or synergistic interactions resulting in antinociception have been reported to occur in the rat formalin paw model of inflammatory pain between -intraperitoneal D 9 -THC and morphine [72]; -intrathecal R-(þ)-WIN55212 and an intrathecally administered a 2 -adrenoceptor agonist (clonidine), cholinesterase inhibitor (neostigmine) or local anaesthetic (bupivicaine) [73,74]; -anandamide and the cyclooxygenase inhibitor, ibuprofen, administered by intraplantar injection [75]; and -HU-210 and the non-steroidal anti-inflammatory drug, acetylsalicylic acid, co-administered systemically [76].…”
Section: Potential Adjunctive Strategies For Cannabinoid Receptor Actmentioning
confidence: 99%
“…However, these interactions are usually only seen at doses of CBD that are as high or higher than the dose of ⌬ 9 -THC, a combination that is not often the case with recreationally available marijuana (e.g., ElSohly et al, 2000). Also, several studies have reported opposite or no such interactions between ⌬ 9 -THC and CBD (e.g., Welburn et al, 1976;Jarbe et al, 1977;Zuardi et al, 1984;Fadda et al, 2004;Finn et al, 2004). Other constituents of marijuana have also been evaluated for their own activity and their ability to modulate the effects of ⌬ 9 -THC.…”
mentioning
confidence: 99%